The socialization of civilians and militia members: Evidence from Guatemala. (September 2017) - Bateson, Regina
When the Guatemalan civil war ended in 1996, the Peace Accords required the demobilization of the civil patrols. Yet, nearly two decades after the end of the war, the ex-patrollers remain organized and active. At first glance, the persistence of Guatemala's civil patrols sounds like a triumph of socialization: the men enrolled in the civil patrols were effectively socialized during the war, so they continue patrolling today. This argument is seductively simple, but it is incorrect. Using process tracing to analyze historical documents and interviews with former civil patrollers, I show that the military did not succeed in socializing most of its patrollers. The military was, however, remarkably successful at socializing civilians in conflict zones. After enduring a ferocious scorched earth campaign followed by re-education, civilians either learned to fear and comply with the military and the civil patrols, or they internalized the military-promulgated narrative that repression is necessary to guarantee security. Both these outcomes facilitate patrolling in postwar Guatemala, where many civilians in war-affected areas either embrace or tolerate extralegal security patrolling as a means of preventing crime from spreading to their communities. Theoretically, the case of Guatemala's civil patrols expands our knowledge of socialization in militias and civil defense forces. Mass socialization of group members is not necessary for an armed group to retain its influence in the long term, even after a conflict has ended. Additionally, socialization occurs not just within groups, but also dynamically and interactively across group boundaries. To fully understand the trajectories of armed groups, it is important to analyze both socialization within armed groups and the socialization of the broader civilian population.